Mineralogyc and physico-chemical characteristics of bentonite clay from Sabah Malaysia - Samsuri, Ariffin; Irawan, Sonny (2005)
This paper presents the results of laboratory work on mineralogy, physico-chemical characteristics the bentonite clay from two areas of Sabah, Malaysia, namely Andrassy and Mansuli. A standard Wyoming bentonite had been used as a potential comparison. This study included mineralogical, chemical composition, cation exchange composition, specific surface area and atterberg limit. The results from mineralogy investigation showed that Sabah bentonite less montmorillonite mineral content that Wyoming. Based on chemical composition, Sabah bentonite has ferrous iron content higher than Wyoming bentonite. Cation exchange capacity (CEC) and specific surface area values of Sabah bentonite is lower than Wyoming bentonite while from atterberg limit Sabah bentonite is closed to the Ca-montmorillonite.